2005
DOI: 10.1038/sj.ijo.0803074
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter, randomized, double-blind, placebo-controlled, dose-finding trial of a long-acting formulation of octreotide in promoting weight loss in obese adults with insulin hypersecretion

Abstract: Objective: To compare changes in weight in obese patients who received long-acting octreotide (octreotide LAR) at one of three dose levels (20, 40, or 60 mg) or placebo over 6 months and to identify the lowest dose of octreotide LAR that safely achieved optimal weight loss. Design: Randomized, double-blind, placebo-controlled trial of octreotide LAR at three dose levels. Patients: A total of 172 adults (28 men and 144 women) with at least moderate obesity (body mass index (BMI) range 30-65 kg/m 2 ) and evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 39 publications
3
66
0
2
Order By: Relevance
“…Moreover, across multiple models, we found that obesity and lipid homeostasis are more sensitive to small changes in circulating insulin levels than glucose homeostasis. Collectively, these experiments also fit well with clinical and pre-clinical studies demonstrating that therapy with long-acting insulin analogues leads to weight gain, and with small trials showing weight loss with drugs that reduce insulin secretion (Alemzadeh et al 1998, Lustig et al 2005, ORIGIN Trial Investigators et al 2012, Skovso et al 2015. For example, a recent investigation reported that chronic insulin infusion via mini-osmotic pump leads to WAT expansion in mice (Rajan et al 2016).…”
Section: :3supporting
confidence: 55%
See 2 more Smart Citations
“…Moreover, across multiple models, we found that obesity and lipid homeostasis are more sensitive to small changes in circulating insulin levels than glucose homeostasis. Collectively, these experiments also fit well with clinical and pre-clinical studies demonstrating that therapy with long-acting insulin analogues leads to weight gain, and with small trials showing weight loss with drugs that reduce insulin secretion (Alemzadeh et al 1998, Lustig et al 2005, ORIGIN Trial Investigators et al 2012, Skovso et al 2015. For example, a recent investigation reported that chronic insulin infusion via mini-osmotic pump leads to WAT expansion in mice (Rajan et al 2016).…”
Section: :3supporting
confidence: 55%
“…Although our published studies have demonstrated that preventing hyperinsulinemia can prevent obesity in euglycemic conditions, we have not yet shown that obesity can be treated by reducing insulin secretion in mice that have already gained weight or demonstrated that hyperinsulinemia has a similar role in a more typical scenario that includes dysglycemia. Clinical evidence to support reducing insulin as a therapy for obesity has been presented (Lunetta et al 1996, Alemzadeh et al 1998, Lustig et al 2005, but conflicting data on specific patient populations have also been published (Brauner et al 2016). Therefore, a focus on hyperinsulinemia as a target for obesity has not yet been widely adopted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ß-cell-targeted genetic intervention in mice protects against obesity, either by the reduction of insulin gene dosage (Mehran et al, 2012) or by the ablation of the amplifying pathway of glucose-stimulated insulin secretion (Vetterli et al, 2016a). Clinical data have shown that pharmacological inhibition of insulin secretion in obese subjects can promote weight loss (Lustig et al, 2006;van Boekel et al, 2008), although drugs used in these studies are associated with undesired side effects, such as hyperglycemia. Weight control by lifestyle modification has a low success rate, therefore calling for alternative therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Some available clinical data do support such observations made in rodents. Indeed, pharmacological inhibition of insulin secretion in obese subjects is accompanied by weight loss [20,21], although such a treatment may be associated with undesired side effects, for example hyperglycemia. Restricting the inhibition of insulin secretion to the only amplifying pathway of the b-cell might potentially prevent such side effects, as demonstrated using a genetic approach [18].…”
Section: Preventing Obesity By the Limitation Of Insulin Secretionmentioning
confidence: 99%